Evaluation of the Parameters Affecting the Photoelectrocatalytic Reduction of CO2 to CH3OH at Cu/Cu2O Electrode - Brito, Juliana Ferreira de [UNESP]; Silva, Alexander Alves da [UNESP]; Cavalheiro, Alberto José [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP] (Esg, 2014)
This work describes the photoeletrocatalytic reducing CO2 dissolved in slightly alkaline solution at Cu/Cu2O electrode prepared by electrochemical deposition of a copper foil in 12.0 mol L-1 submitted to voltage of -0.40 V for 30 min. The effect of supporting electrolyte was investigated and 80 ppm of methanol was generated when photoelectrolysis were performed at Cu/Cu2O electrode in 0.1 mol L (-1) Na2CO3/NaHCO3. However, this value is limited to 10 ppm in Na2CO3 and is almost neglected in NaHCO3. The bias potential also plays an important role in the formation of methanol by photoelectrocatalysis, where is maxima at applied potential of 0.2V and nil at -0.4V. Maximum photoconversion of CO2/CH3OH was obtained at pH 8, which is successively suppressed in an alkaline medium. Thus, using the best experimental conditions of 0.1 mol L-1 Na2CO3/NaHCO3, pH 8, were obtained 75 % reduction of CO2 to methanol under UV-Vis irradiation and bias potential of +0.2 V vs Ag/AgCl, after 2 hours of treatment. The results illustrate that the stabilization of Cu (I) on the electrodic material seems to be the key to success in this photoelectrochemical reaction.
Keywords: Cu/Cu2O semiconductor; CO2 reduction; methanol; photoelectrocatalytic reduction; carbon dioxide conversion to methanol